Effect of Parents and Teachers Support on Students’ Mathematics Achievement - Nurfajrin, Tria Ermina; Susetyo, Budi; Indahwati, NFN; Rahmawati, NFN (Indonesian Journal of Educational Assessment, 2021)
The purpose of this study was to analyze the effect of parents’ and teachers’ support on students’ mathematics achievement. This study used AKSI 2019 survey data in mathematics and examined 12 aspects of parents’ and teachers’ support. Data from AKSI survey is nested. The method for nested data is Multilevel Analysis or Hierarchical Linear Model (HLM). The results of this study concluded that parents’ education, the interaction between teacher and student, teacher’s appreciation, problem-solving and creative thinking given by the teacher, teacher’s communication, teacher’s feedback on student assignment, teachers’ encouragement, and parents attitudes toward activities with student affects students’ mathematics achievement.